2019
DOI: 10.3389/fpls.2019.00815
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Addition Increases the Sensitivity of Photosynthesis to Drought and Re-watering Differentially in C3 Versus C4 Grass Species

Abstract: Global change factors, such as variation in precipitation regimes and nitrogen (N) deposition, are likely to occur simultaneously and may have profound impacts on the relative abundance of grasses differing in functional traits, such as C 3 and C 4 species. We conducted an extreme drought and re-watering experiment to understand differences in the resistance and recovery abilities of C 3 and C 4 grasses under different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 93 publications
(137 reference statements)
3
26
0
Order By: Relevance
“…(2013) and Zhong et al . (2019). The sampled plant materials were washed with deionized water three times, oven‐dried and mixed together before being ball‐milled to powder for the measurement of their N and P concentrations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2013) and Zhong et al . (2019). The sampled plant materials were washed with deionized water three times, oven‐dried and mixed together before being ball‐milled to powder for the measurement of their N and P concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…The other half was sampled in early November 2017, when the plants had turned completely yellow. For each experiment, the upper second and third most fully expanded leaves and culms were sampled as outlined by Lü et al (2013) and Zhong et al (2019). The sampled plant materials were washed with deionized water three times, oven-dried and mixed together before being ball-milled to powder for the measurement of their N and P concentrations.…”
Section: Plant Sample Collectionmentioning
confidence: 99%
“…Zhong et al [35] studied the effect of N addition on the sensitivity of photosynthesis among C 3 versus C 4 grass species under extreme drought and re-watering conditions. Their results concluded that N addition resulted in an increase in biomass, but photosynthesis resilience was lower under drought conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Zhong et al [36] studied the effect of N addition on the sensitivity of photosynthesis among C3 versus C4 grass species under extreme drought and rewatering conditions. Their results concluded that N addition resulted in an increase in biomass, but photosynthesis resilience was lower under the drought conditions.…”
Section: Since Elevated Co2 [Eco2] Is One Of the Documented Global Chmentioning
confidence: 99%